PERLAKUAN PRA PANEN TANAMAN KENIKIR (Cosmos caudatus Kunth.) dengan PENYEMPROTAN KALSIUM KLORIDA (CACL2) pada BEBERAPA MODEL BUDIDAYA - zuhanid zamarudah; Siti Asmaniyah Mardiyani; Siti Muslikah (AGRONISMA, 2021)
This study aims to determine the effect of the interaction between the concentration of CaCl2 and the cultivation model on the growth and yield of kenikir (Cosmos caudatus Kunth.) plants. This research was conducted to determine the effect of increasing the concentration of CaCl2 and the cultivation model on the growth, yield, and quality of kenikir (Cosmos caudatus Kunth.) This research was conducted on Jl. Joyo Agung, Merjosari, Kec. Lowokwaru, Malang City and Central Laboratory, the Islamic University of Malang from February 2021 to April 2021. This study used a Factorial Randomized Block Design (RAK) with 2 factors and was repeated 3 times. Observational data were analyzed using the 5% F test (ANOVA). If there is a significant effect, then further tests are carried out with BNJ (Honest Significant Difference) at 5% level and BNT (Least Significant Difference). Parameters observed were: plant height, number of leaves, stem diameter, number of shoots, leaf length, leaf width, total fresh weight, economic weight, dry weight, root length, weight loss, vitamin C, total dissolved solids (TPT), water and chlorophyll content. The results showed that there was an interaction effect between the concentration of CaCl2 and the cultivation model on the number of leaves and root length. The 5% concentration of CaCl2 treatment showed high chlorophyll content and root length, pre-harvest CaCl2 administration did not affect the vegetative growth of kenikir plants. While the treatment of the cultivation model showed that the application of fertilizer was better than without fertilizer on plant growth and yield.